Business Activities Based on Business Model Canvas in Importance of Tourism Village - Ratna Devi Sakuntalawati; Isyadul Ibad (Universitas Sebelas Maret, 2024)
The business activities in Pentingsari tourism village have yet to maximize profits for the village community fully. This research aims to develop a business activity model based on the Business Model Canvas (BMC) to enhance tourism management. Utilizing David Clark's capability theory, the study employs a quantitative approach, survey methods, and explanatory research. A census of 127 heads of households was conducted as respondents. Four variables are examined: two exogenous and two endogenous, analyzed through path analysis. Path coefficients were estimated using regression statistics with SPSS 25. The findings indicate that community empowerment in tourism management (X1) significantly influences the level of business activity (Y2) through collaboration among business actors (Y1), with a path coefficient of 0.734, supporting the hypothesis (Ha). Additionally, achieving aspirations related to welfare (X2) impacts the level of business activity (Y2) via cooperation between business actors (Y1), with a path coefficient of 0.703, also supporting the hypothesis (Ha). Consequently, a business activity model based on the BMC was established. In conclusion, enhancing business activities in Pentingsari tourism village is contingent upon community empowerment in tourism management and achieving community welfare aspirations facilitated through collaborative efforts among business actors.Keywords: achievement aspirations; business activity; BMC; community empowerment; tourism villages